Language shift in a majority ethnolinguistic speech group : a case study of Kadazandusun families in Sabah - Esther, Jawing (Universiti Malaysia Sarawak, UNIMAS, 2006)
Language shift for multiethnic speech communities may result in the mother tongue being no longer spoken within the community itself. The purpose of this study is to investigate the nature of intergenerational shift in language use within the Kadazandusun families. The aims of this study are to find out the language(s) used by different generations of speakers and for what purpose(s) the language(s) is/are used, the factors that motivate certain language choice that leads to language shift and finally, to examine the use of Kadazandusun language in relation to the value of ethnic identity. This study is a case study of five Kadazandusun families where general observation has shown the rapid use of another language in family domain. The methodology employed is one of interview and participant observation to study the social phenomenon from the participants' perspectives. The results show that only the first and second generations speak Kadazandusun as their mother tongue whereas almost all of the third and fourth generations speak Sabah Local Malay and/or English as their mother tongue. Sabah Local Malay and/or English have taken over some of the communicative functions of Kadazandusun in the family domain. Secondly, the extent to which individuals in the speech community have changed their habitual language use varies considerably according to a range of factors such as education, intermarriage, prestige, relocation and language contact. These factors accelerate the shift from the use of Kadazandusun language to other languages. Finally, a majority ofthe younger respondents (Generation 2 and 3) under study value the importance of Kadazandusun language as the marker oftheir ethnic identity. The findings are applicable to the context of this case and other contexts that are similar to the setting ofthe study.